Dynamics of groundwater‐derived nitrate and nitrous oxide in a tidal estuary from radon mass balance modeling. (27th August 2013) - Wong, Wei Wen; Grace, Michael R.; Cartwright, Ian; Cardenas, M. Bayani; Zamora, Peter B.; Cook, Perran L. M.
Abstract : We monitored submarine groundwater discharge (SGD) into the Werribee Estuary, Australia, using both chemical and physical methods. SGD occurred at hotspots where 222 Rn persisted through a 12 month survey period. A significant correlation between 222 Rn and ( r 2 = 0.8, p < 0.01), as well as between 222 Rn and N2 O ( r 2 = 0.6, p < 0.01) at a 222 Rn hotspot, and much higher and N2 O concentrations in groundwater relative to surface water suggest that elevated and N2 O concentrations in the estuary were derived from SGD. Two sampling campaigns over 24 h revealed that variations of 222 Rn, , and N2 O were controlled by tide‐induced hydraulic‐head gradient fluctuations and, possibly to a much lesser extent, by tidal pumping and density‐driven convection. A two‐box 222 Rn mass‐balance model was used to calculate the rate of SGD into two different layers across the pycnocline of the estuary. A higher total groundwater discharge rate of 0.12 ± 0.09 m d −1 was observed in the surface layer during ebb tide compared with 0.10 ± 0.08 m d −1 during flood tide. Fluxes of groundwater‐derived and N2 O were higher than the riverine flux at baseflow by more than 30 fold and 20 fold, respectively. SGD derived fluxes exceeded the mean annual riverine and TN fluxes by a factor of ∼ 5 and ∼ 3 respectively. SGD‐derived N2 O fluxes were 170 µmol m −2 d −1, which are among the highest N2 O fluxes observed in estuaries.